Preventing transient parametric instabilities in high power gravitational wave detectors using thermal transient compensation. (29th June 2017) - Jaberian Hamedan, V; Blair, C; Liu, J; Bossilkov, V; Zhao, C; Ju, L; Blair, D G
Abstract: Laser interferometer gravitational wave detectors such as Advanced LIGO use large fused silica test masses in which temperature perturbations take many hours to reach dynamic equilibrium. When environmental disturbances cause the optical cavities to lose optical power there is a sudden thermal transient which causes the mirror profile to change significantly over time. This causes time dependent tuning of transverse optical mode frequencies, some of which cause parametric instability. These transient parametric instabilities greatly increase the complexity of active control of parametric instability. Here we report on modeling and testing of a system in which a low power C O 2 laser is designed to maintain a constant heat flux when cavity power is lost, thereby enabling thermal transients to be minimized and cavity locking to be re-established. We demonstrate a reduction in the thermal transient in the optical mode spacing to <3 % of the transient without compensation. For advanced LIGO this would reduce the complexity of control systems for controlling parametric instabilities.